Integrating a novel tactic, long-lasting insecticide-incorporated netting into integrated pest management programs for food facilities - Ranabhat, Sabita (My University, 2024)
Stored products play a significant role in both the economy and global food security. However, as stored products proceed through the post-harvest supply chain, stored product insects readily attack them, resulting in reduced quality and quantity of food. Pest management after harvest has relied heavily on fumigation to combat infestations. However, fumigant options have become limited due to increasing insect resistance to phosphine, and regulatory restrictions on the use of methyl bromide in most settings due to its harmful impact on the ozone layer. Further, there is increasing consumer demand for products with minimal or no insecticide usage throughout the supply chain after harvest. Thus, there has been a push to diversify integrated pest management programs (IPM) after harvest. One way to intercept insects from the landscape is by using long-lasting insecticide-incorporated netting (LLIN). Prior work has found that LLIN causes lethal and sublethal effects in multiple stored product insects. Nonetheless, there is a need by stakeholders to understand whether LLIN can support phosphine resistance management programs. In addition, it is important to understand how to integrate LLIN into comprehensive IPM programs with existing tactics at food facilities, such as fumigation and residual insecticide usage. Further, it is crucial to know whether LLIN deployment can affect the long-term dynamics of stored product insects at food facilities. My project aims to expand the use of LLIN in the post-harvest supply chain by addressing these concerns directly. Using video-tracking and Ethovision software, I have found exposure to deltamethrin LLIN for 0.5, 2, or 60 min resulted in substantial and equally adverse mobility reductions for phosphine-resistant and phosphine-susceptible strains of Tribolium castaneum Herbst (Coleoptera: Tenebrionidae) and Rhyzopertha dominica Fabricius (Coleoptera: Bostrichidae). In addition, when assessing deltamethrin, permethrin, indoxacarb, and dinotefuran on surrogate netting at 1%, most active ingredients (a.i.) were found to suitably induce mortality in both strains of T. castaneum and R. dominica. I also assessed the movement of larval and adult sexed dermestids (Trogoderma variabile Baillon [Coleoptera: Dermestidae] and T. inclusum Le Conte) in the presence of food kairomones and pheromones ((Z)-14-methyl-8-hexedecenal) after exposure to LLIN or control netting. Generally, the olfaction and orientation of larval dermestids were affected after exposure to LLIN compared to control netting. Overall, out of 40 possible olfactory and taxis patterns which could be disrupted, exposure to LLIN interrupted 68–73% of these in adult T. inclusum and T. variabile, respectively, compared to control netting-exposed individuals. Our study suggests the use of LLIN may enhance the effectiveness of other concurrent behaviorally-based strategies. Further, in a field bulk storage experiment over two years, data demonstrated that LLIN can reduce the number of fumigations required by 68–91% while reducing insect dispersal and progeny production by 83–99% and 89–99%, respectively. This consistently shows that LLIN use can enhance fumigation by reducing reliance on it and making the remaining fumigations more effective. Further, our data showed there is a marginal boost of combining LLIN with two common residual insecticides, CentanylTM EC (a.i. deltamethrin), and Evergreen® (a.i. natural pyrethrins), translating to 10–20% fewer T. castaneum progeny produced. Finally, I modeled the stage-structured dynamics of T. castaneum at food facilities with and without two types of LLIN and showed that deploying LLIN may contribute to the local extirpation of T. castaneum within as few as 15 generations. Therefore, LLIN (whether deltamethrin or alpha-cypermethrin) shows promise as a new way to combat stored product pests in and around food facilities, while diversifying pest management programs, and is compatible with existing tactics. My research should help to speed the adoption of LLIN by stakeholders at food facilities while helping increase the sustainability of IPM after harvest.
Keywords: Agriculture; Post-harvest; Stored product insects; Insecticides; Netting; Integrated pest management; Food security